Brain serotonin 4 receptor binding is associated with the cortisol awakening response. (May 2016) - Jakobsen, Gustav R.; Fisher, Patrick M.; Dyssegaard, Agnete; McMahon, Brenda; Holst, Klaus K.; Lehel, Szabolcs; Svarer, Claus; Jensen, Peter S.; Knudsen, Gitte M.; Frokjaer, Vibe G.
Highlights: We performed a cross-sectional study to evaluate the association between brain serotonin 4 receptor binding and HPA-axis dynamics in healthy individuals. We demonstrate a robust negative association between brain serotonin 4 receptor binding and the cortisol awakening response. Our results reinforce an association between serotonin signalling and HPA-axis function in the human brain. We suggest that serotonergic neurotransmission support HPA-axis dynamics in healthy individuals. Abstract: Serotonin signalling is considered critical for an appropriate and dynamic adaptation to stress. Previously, we have shown that prefrontal serotonin transporter (SERT) binding is positively associated with the cortisol awakening response (CAR) (Frokjaer et al., 2013 ), which is an index of hypothalamic–pituitary–adrenal (HPA)-axis output dynamics. Here, we investigated in healthy individuals if cerebral serotonin 4 receptor (5-HT4r) binding, reported to be a proxy for serotonin levels, is associated with CAR. Thirty healthy volunteers (25 males, age range 20–56 years) underwent 5-HT4r PET imaging with [ 11 C]-SB207145, genotyping of the SERT-linked polymorphic region (5-HTTLPR), and performed serial home sampling of saliva (5 time points from 0 to 60 min from awakening) to assess CAR. The association between 5-HT4r binding in 4 regions of interest (prefrontal cortex, anterior cingulate cortex, pallidostriatum, and hippocampus) and CAR was tested using multiple linear regression with adjustment for age and 5-HTTLPR genotype. Finally, an exploratory voxel-based analysis of the association was performed. CAR was negatively associated with 5-HT4r binding in pallidostriatum ( p  = 0.01), prefrontal cortex ( p  = 0.03), and anterior cingulate cortex ( p  = 0.002), respectively, but showed no association in hippocampus. The results remained significant when taking into account other potentially relevant covariates. In conclusion, our finding reinforces an association between HPA-axis function and serotonin signaling in vivo in humans. We suggest that higher synaptic serotonin concentration, here indexed by lower 5-HT4r binding, supports HPA-axis dynamics, which in healthy volunteers is reflected by a robust CAR.